Probing the energy landscape of the lipid interactions of the serotonin 1A receptor - Mohole, Madhura; Naglekar, Amit; Sengupta, Durba; Chattopadhyay, Amitabha (Biophysical Chemistry, 2024)
G protein-coupled receptors (GPCRs) are lipid-regulated transmembrane proteins that play a central role in cell signaling and pharmacology. Although the role of membrane lipids in GPCR function is well established, the underlying GPCR-lipid interactions have not been thermodynamically characterized due to the complexity of these interactions. In this work, we estimate the energetics and dynamics of lipid association from coarse-grain simulations of the serotonin1A receptor embedded in a complex membrane. We show that lipids bind to the receptor with varying energetics of 1-4 kT, and timescales of 1-10 mu s. The most favorable energetics and longest residence times are observed for cholesterol, glycosphingolipid GM1, phosphatidylethanolamine (PE) and phosphatidylserine (PS) lipids. Multi-exponential fitting of the contact probability suggests distinct dynamic regimes, corresponding to ps, ns and mu s timescales, that we correlate with the annular, intermediate and nonannular lipid sites. The timescales of lipid binding correspond to high barrier heights, despite their relatively weaker energetics. Our results highlight that GPCR-lipid interactions are driven by both thermodynamic interactions and the dynamical features of lipid binding.
Keywords: GPCR-lipid interactions; Lipid energetics; Lipid residence time; Molecular dynamics simulations; Serotonin 1 a receptor